GAMBARAN INTENSITAS NYERI PASCAOPERASI PADA PASIEN YANG MENJALANKAN TINDAKAN OPERASI ELEKTIF DI RSU HAJI MEDAN - MURIZZALDI YUSSUF; MUHAMMAD JALALUDIN ASSUYUTHI CHALIL (LP2MTBM MAKARIOZ, 2022)
Pain is an unpleasant feeling and emotional experience related to actual tissue damage or situations that describe the condition of the damage. The four biggest causes of pain are cancer, osteo/rheumatoid arthritis, arthritis, surgery and injury, which make up the etiology of pain complex. Surgery or surgery is an invasive treatment by opening or exposing parts of the body that would normally cause discomfort or pain after the procedure. To see a picture of postoperative pain intensity in patients undergoing elective surgery at RSU Haji Medan. This study is an observational analytic study with cross sectional design with a sample size of 38 people and uses the Numeric Rating Scale (NRS) instrument. The data were processed using univariate analysis and bivariate analysis, which would then be described by looking at the presentation of the representation of each variable in the form of a frequency distribution table. Based on preoperative respondents, the greatest pain intensity was pain in adults as many as 11 people (50.0%). While patients with 24 hours postoperative pain, moderate pain intensity was the most according to the patient, namely 14 people (63.6%). Based on the type of anesthesia, it was found that the type of general anesthesia was the most widely used type of anesthesia among respondents who said 30 people (78.9%). Based on the type of elective surgery, the largest type of surgery performed was abdominal surgery, which was 13 people (34.2%). In the analysis, the results obtained were p value = 0.000 (p value <0.05), which indicates that there was a significant decrease in the pain intensity of patients after surgery in the first 24 hours compared to the pain intensity before surgery. In this study it can be concluded that postoperative pain felt before surgery.